Proteases from a species of the Trichocomaceae family for application in the food industry (Research, Society and Development, 2022)
Proteases are plant, animal and microbial enzymes of high economic and biotechnological value. Among these, we can highlight proteases produced by fungal species. The present study aimed to analyze the production of proteases by Aspergillus clavato flavus DPUA 929. The matrix culture was prepared in Sabouraud Agar, with yeast extract 0.5% (w/v). The bioprocess was carried out for 7 days at 150 rpm at 25 °C. To determine the proteolytic activity, 1% Azocasein (w/v) was used as substrate. In analyses of partial characterization, the effect of pH and temperature were evaluated, according to the experimental protocol. The results revealed that Aspergillus clavato flavus 929 produce proteases equivalent to 21.12 U/ml, and in the enzyme characterization tests, the maximum proteolytic activity was determined at pH 6.0 and at 50 ºC. These data demonstrate that Aspergillus clavato flavus produce different proteases of industrial importance in conditions analyzed here.